# Integral $\int \frac{\sqrt{\sin x}}{\sqrt{\sin x} + \sqrt{\cos x}} dx$

We have to evaluate the following integral:

$$\int \frac{\sqrt{\sin x}}{\sqrt{\sin x} + \sqrt{\cos x}} dx$$

I tried this:

I multiplied both the numerator and denominator by $\sec x$
And substituted $\tan x = t$.

But after that I got stuck.

The book where this is taken from gives the following as the answer: $$\ln(1+t)-\frac14\ln(1+t^4)+\frac1{2\sqrt2}\ln\frac{t^2-\sqrt2t+1}{t^2+\sqrt2t+1}-\frac12\tan^{-1}t^2+c$$ where $t=\sqrt{\cot x}$

• Are you sure it is not a definite integral?
– user371838
Commented Jan 8, 2017 at 6:00
• @Rohan It doesn't have limits, so it must be indefinite Commented Jan 8, 2017 at 6:01
• The indefinite integral is not nice to calculate, the answer if far too large, and involves many elliptic functions. Even Wolfram alpha won't calculate it: wolframalpha.com/input/… Commented Jan 8, 2017 at 6:02
• It's possible with elementary functions. Commented Jan 8, 2017 at 6:04
• @Rohan the answer given in my book as i.imgur.com/qHhVFpe.jpg Commented Jan 8, 2017 at 6:04

$\displaystyle \mathcal{I} = \int\frac{\sqrt{\sin x}}{\sqrt{\sin x}+\sqrt{\cos x}}dx = \int \frac{\sqrt{\tan x}}{1+\sqrt{\tan x}}dx$

substitute $\tan x= t^2$ and $\displaystyle dx = \frac{1}{1+t^4}dt$

$\displaystyle \mathcal{I}= \int\frac{t}{(1+t)(1+t^4)}dt = \frac{1}{2}\int\frac{\bigg((1+t^4)+(1-t^4)\bigg)t}{(1+t)(1+t^4)}dt$

$\displaystyle = \frac{1}{2}\int\frac{t}{1+t}dt+\frac{1}{2}\int\frac{(t-t^2)(1+t^2)}{1+t^4}dt$

$\displaystyle = \frac{1}{2}\int \frac{(1+t)-1}{1+t}dt+\frac{1}{2}\int \frac{t+t^3-(t^2-1)-t^4-1}{1+t^4}dt$

$\displaystyle =-\frac{t}{2}+\frac{1}{2}\ln|t+1|+\frac{1}{4}\int\frac{2t}{1+t^4}+\frac{1}{2}\int\frac{t^3}{1+t^4}dt-\frac{1}{2}\int \frac{t^2-1}{1+t^4}dt-\frac{1}{2}t+\mathcal{C}$

all integrals are easy except $\displaystyle \mathcal{J} = \int\frac{t^2-1}{1+t^4}dt = \int\frac{1-t^{-2}}{\left(t+t^{-1}\right)^2-2}dt = \int\frac{(t-t^{-1})'}{(t-t^{-1})^2-2}dt$

• if we substitute $\tan x= t^2$ then $\displaystyle dx = \frac{2t}{1+t^4}dt$ Commented Jun 9, 2020 at 13:46
• Isn't it $\frac{2t^2}{(1+t)(1+t^4)}$ when $\tan x = t^2$? I think you used $\cot x = t^2$ (an answer by @openspace below).
– Vue
Commented Feb 9, 2022 at 2:26

We rationalise the denominator to get $$I =\int \frac {\sin x-\sqrt {\cos x\sin x}}{\sin x-\cos x} dx$$ Writing everything in terms of $\cot x$, we get $$I =\int \mathrm{csc}^2 x\left(\frac {\sqrt {\cot x}-1}{\cot^3 x-\cot^2 x+\cot x-1}\right) dx$$ Now substituting $u=\cot x$ and further $v=\sqrt {u}$ gives us $$I = -\int\frac {2v }{v^5+ v^4 + v+1} dv$$ Performing a partial fraction decomposition we have $$I = \frac {2}{4-4\sqrt {2}}\int \frac {v +\sqrt {2}-1}{v^2 +\sqrt {2}v +1} dv +\frac {2}{4+4\sqrt {2}}\int \frac {v-\sqrt {2}-1}{v^2-\sqrt {2 }v+1} dv+\int \frac {1}{1+v} dv =I_1 +I_2 +I_3$$ Hope you can take it from here.

HINT multiply nominator and denominator by $\frac{1}{\sqrt{sin(x)}}$, then $t = \sqrt{cot(x)}$ after all you'll have $\displaystyle\frac{2t}{(t^4 + 1)(t+1)}$

• After that does we have to substitue t = sin k Commented Jan 8, 2017 at 6:10
• @koolman I have no this substitution in my hint. Commented Jan 8, 2017 at 6:12
• I mean what we have to after$\displaystyle\frac{2t}{(t^4 + 1)(t+1)}$ Commented Jan 8, 2017 at 6:14
• @koolman we could represent this as sum of polynomials with denominators $t^4 + 1$ and $t + 1$ Commented Jan 8, 2017 at 6:16

For the sake of exploring other options, consider the substitution

$$y = \frac{\sqrt{\sin x}}{\sqrt{\sin x}+\sqrt{\cos x}} = \frac{\sqrt{\tan x}}{\sqrt{\tan x}+1} \implies x = \arctan \frac{y^2}{(1-y)^2}$$

so $$0; then

$$\int \frac{\sqrt{\sin x}}{\sqrt{\sin x}+\sqrt{\cos x}} \, dx = \int \frac{2(1-y)y^2}{1-4y+6y^2-4y^3+2y^4} \, dy$$

The denominator can be expressed as a difference of squares and subsequently as a product of quadratic polynomials with real coefficients,

\begin{align*} & 1-4y+6y^2-4y^3+2y^4 \\ &= (1-y)^4 + y^4 \\ &= (1-y)^4 \color{red}{+ 2(1-y)^2y^2} + y^4 \color{red}{- 2(1-y)^2y^2} \\ &= \left[(1-y)^2 + y^2\right]^2 - 2(1-y)^2y^2 \\ &= \left((1-y)^2 + y^2 \color{red}+ \sqrt2\,(1-y)y\right) \left((1-y)^2 + y^2 \color{red}- \sqrt2\,(1-y)y\right) \\ &= \left(1 - (2-\sqrt2)y + (2-\sqrt2)y^2\right) \left(1 - (2+\sqrt2)y + (2+\sqrt2)y^2\right) \end{align*}

and hence the integrand can be decomposed into

$$\frac1{\sqrt2} \left[\frac y{1 - (2+\sqrt2)y + (2+\sqrt2)y^2} - \frac y{1 - (2-\sqrt2)y + (2-\sqrt2)y^2} \right]$$

For $$0 (which contains $$2\pm\sqrt2$$), we may use the elementary result

\begin{align*} & \int \frac{y}{1-ay+ay^2} \, dy \\ &= \frac1{\sqrt{4a-a^2}} \arctan \left(\sqrt{\frac a{4-a}} (2y-1)\right) + \frac1{2a} \log\left\lvert1-ay+ay^2\right\rvert + C \end{align*}

$$\displaystyle\int\frac{\sqrt{\sin x}dx}{\sqrt{\sin x}+\sqrt{\cos x}}\;=\;\int\frac{dx}{1+\sqrt{\cot x}},\\ \displaystyle\cot x=z^{2} \;\;\Rightarrow\;\; -(1+z^{2})dx=2zdz,\\ \displaystyle\int\frac{dx}{1+\sqrt{\cot x}} \;=\; -\int\frac{2zdz}{(1+z^{2})(1+z)} \;=\; -2\int\frac{z(z-1)dz}{z^{4}-1}.\\ \displaystyle\frac{z}{z^{4}-1}\;=\;\frac{1}{2}\left( \frac{z}{z^{2}-1}-\frac{z}{z^{2}+1} \right),\\ \displaystyle\frac{z^{2}}{z^{4}-1}\;=\;\frac{1}{2}(\frac{1}{z^{2}-1}+\frac{1}{z^{2}+1}),\\ \displaystyle\frac{z^{2}-z}{z^{4}-1}=\frac{1}{2}(\frac{1-z}{z^{2}-1})+\frac{1}{2}(\frac{1}{z^{2}+1}+\frac{z}{z^{2}+1})=-\frac{1}{2(z+1)}+\frac{1}{2}(\frac{1}{z^{2}+1}+\frac{z}{z^{2}+1}).\\ \displaystyle-2\int\frac{z(z-1)dz}{z^{4}-1}\;=\;\ln\left| z+1 \right|-\arctan{z}-\ln\sqrt{z^{2}+1}+c,\\ \displaystyle\int\frac{\sqrt{\sin x}dx}{\sqrt{\sin x}+\sqrt{\cos x}}\;=\;\ln\left(\frac{\sqrt{\cot{x}}+1}{\sqrt{\cot{x}+1}} \right)-\arctan{\sqrt{\cot{x}}}+c.$$

• $-(1+z^{2})dx=2zdz$ is questionable; so is the result Commented Aug 23, 2022 at 13:34